2021
DOI: 10.1111/1365-2435.13863
|View full text |Cite
|
Sign up to set email alerts
|

Physical adaptations of butterfly proboscises enable feeding from narrow floral tubes

Abstract: 1. Butterflies use a proboscis, a microfluidic probe engineered by natural selection, to feed on nutritive fluids. The structural configuration of proboscises relates to feeding habits; however, the adaptations that enable proboscis entry into narrow floral corollas lack experimental evidence.2. Here, we investigated proboscis adaptations that enable entry into corollas using funnel-shaped glass capillary tubes and performed feeding trials with six butterfly species of different feeding habits. Proboscises wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
(74 reference statements)
5
17
0
Order By: Relevance
“…(c) Blue signals were identified as regions containing high proportions of resilin, or related proteins. These studies were performed on wings 106 , foot attachment devices and legs 107 109 , mouthparts 38 , 110 , or genitals 111 , 112 . The proposed relationship between emitted autofluorescence signal, received by following the protocol 49 , and the mechanical properties was previously cross-validated by AFM-nanoindentation for the hair of foot attachment devices in a lady bird beetle 107 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Blue signals were identified as regions containing high proportions of resilin, or related proteins. These studies were performed on wings 106 , foot attachment devices and legs 107 109 , mouthparts 38 , 110 , or genitals 111 , 112 . The proposed relationship between emitted autofluorescence signal, received by following the protocol 49 , and the mechanical properties was previously cross-validated by AFM-nanoindentation for the hair of foot attachment devices in a lady bird beetle 107 .…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge about material properties complements morphology and gives rise to a profound understanding of function and also—when feeding structures are studied comparatively—of trophic specialisations. For invertebrate feeding structures, only very few studies comparing multiple taxa in the light of trophic specialisation implement both material properties and morphology [for fly teeth, see 37 ; for butterfly proboscises, see 38 and for radular teeth, see 39 – 43 .…”
Section: Introductionmentioning
confidence: 99%
“…to be an adaptation for optimized nectar uptake in nymphalid butterflies (Lehnert et al, 2021). A similar morphology has been described in Hesperiidae as well as long-proboscid Riodinidae (Bauder et al, 2013;Krenn & Bauder, 2017) and seems to be a feature displayed by all nectar-consuming Lepidoptera that are adapted to particularly long nectar spurs (Bauder & Karolyi, 2019).…”
Section: Adaptations Of the Drinking Regionmentioning
confidence: 54%
“…Although there was a lack of inorganic elements in the cuticle of prestomal teeth, confocal microscopy and nanoindentation revealed that the teeth are hard. Confocal microscopy has been used on several arthropods to assess their material properties [3,27,[48][49][50]. Here, the labellum of all studied species had blue autofluorescence, an indicator of the elastomeric protein resilin.…”
Section: Prestomal Teeth Materials Properties In Relation To Feeding ...mentioning
confidence: 99%
“…Insect mouthparts provide notable examples of structure-function relationships [1][2][3], convergent evolution [4][5][6], and coevolution [7][8][9]. The mouthparts of adult flies (Diptera, +150,000 species) are no exception and exhibit adaptations for feeding on a wide variety of liquid foods, including nectar, blood, sweat, and fluids on carrion, dung, and rotting fruit [1,10,11].…”
Section: Introductionmentioning
confidence: 99%